Policing the Domestic Violence Act: teething troubles or system failure - ARTZ, LILLIAN (Agenda (Durban), 2001)
LILLIAN ARTZ writes that the inconsistent and faulty application of the law by the police and other criminal justice agents, has in many cases illustrated that progressive legislation, such as the Domestic Violence Act, can be more of a theoretical exercise than a pragmatic one